2011
DOI: 10.1007/s00421-010-1813-z
|View full text |Cite|
|
Sign up to set email alerts
|

Effects of static contraction and cold stimulation on cardiovascular autonomic indices, trapezius blood flow and muscle activity in chronic neck–shoulder pain

Abstract: The aim of the present study was to investigate reactions in trapezius muscle blood flow (MBF), muscle activity, heart rate variability (HRV) and systemic blood pressure (BP) to autonomic tests in subjects with chronic neck-shoulder pain and healthy controls. Changes in muscle activity and blood flow due to stress and unfavourable muscle loads are known underlying factors of work-related muscle pain. Aberration of the autonomic nervous system (ANS) is considered a possible mechanism. In the present study, part… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
47
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 43 publications
4
47
1
Order By: Relevance
“…Four of the six studies did not find significant differences between the groups (Johnston et al, 2008a;Nilsen et al, 2006;Sjors et al, 2009;Voerman et al, 2007). Hallman et al (2011) found larger UT activity in patients with neck pain during a Cold Pressor Test. Sjogaard et al (2010) found also higher UT activity in the neck pain group while Voerman et al (2007), using a similar task, did not find significant differences between patients with neck pain and healthy controls.…”
Section: Emg Muscle Amplitudementioning
confidence: 89%
See 3 more Smart Citations
“…Four of the six studies did not find significant differences between the groups (Johnston et al, 2008a;Nilsen et al, 2006;Sjors et al, 2009;Voerman et al, 2007). Hallman et al (2011) found larger UT activity in patients with neck pain during a Cold Pressor Test. Sjogaard et al (2010) found also higher UT activity in the neck pain group while Voerman et al (2007), using a similar task, did not find significant differences between patients with neck pain and healthy controls.…”
Section: Emg Muscle Amplitudementioning
confidence: 89%
“…Seven studies measured the activity of the UT during rest. Six studies (Andersen et al, 2014(Andersen et al, , 2008Hallman et al, 2011;Nilsen et al, 2006;Voerman et al, 2007;Wegner et al, 2010) showed consensus and did not find any difference in EMG amplitude between patients with neck pain and healthy controls during rest. In contrast, the study of Sjors et al (2009) found higher activity in patients with neck pain during rest, in comparison to healthy controls.…”
Section: Emg Muscle Amplitudementioning
confidence: 91%
See 2 more Smart Citations
“…13 Agiovlasitis et al 24 found increased low frequency activity during isometric exercise compared with the resting condition in paraplegic patients. Hallman et al 25 investigated the response of cardiac autonomic modulation in isometric contraction in patients with muscle pain, and found a reduction in the overall modulation of HR analyzed through the SDNN index as the intensity of pain increased. Shiro et al 26 found no significant changes in the LF/HF ratio in patients with pain in the trapezius muscle, concluding that the decrease in muscle blood flow and oxygen in the trapezius muscles can derive from the sympathetic response during isometric exercise.…”
Section: B Discussionmentioning
confidence: 99%